Covid-19: desafíos y oportunidades para el aprendizaje en línea: Covid-19: Challenges and Opportunities for Online Learning - Dávila Morán, Roberto Carlos; Ruiz Nizama, José Leonor; González González, José Ignacio (Universidad del Zulia, 2021)
The World Health Organization has declared Covid-19 a pandemic that has represented a contemporary threat to humanity. This pandemic has successfully forced the global shutdown of various activities, including educational ones, and this has resulted in a tremendous migration of universities in response to crisis with online learning as an educational platform. Crisis response migration methods of universities, faculty and students, challenges and opportunities were discussed and it is clear that online learning is different from emergency remote teaching, online learning will be more sustainable while instructional activities they will become more hybrid as long as the challenges experienced during this pandemic are well explored and transformed into opportunities.